Representasi Pendidikan Karakter dalam Pembelajaran Bahasa Indonesia pada Siswa Kelas VIII SMPN 26 Makassar - Mursalin, Awal Jum’a; Mayong, Mayong; Saleh, Muhammad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the values ​​of character education and the methods used by teachers to instill these values ​​in Indonesian language learning for eighth-grade students at SMPN 26 Makassar. This study used a qualitative approach with data collection techniques through observation, interviews, and documentation. The results indicate that eight main character values ​​are integrated into Indonesian language learning: religiousness, tolerance, honesty, discipline, independence, hard work, peace-loving, and responsibility. These values ​​are not taught separately but are internalized through learning activities such as reading, writing, discussions, and group work. The methods used by teachers to instill character include storytelling, discussions, assignments (recitations), and projects. These methods are selected based on the desired character development and are tailored to the learning material. These findings confirm that Indonesian language learning at SMP Negeri 26 Makassar has been implemented holistically, not only developing cognitive abilities but also contributing significantly to student character formation.